Evaluating the efficacy of breastfeeding guidelines on long‐term outcomes for allergic disease. Issue 5 (21st January 2016) - Bion, V.; Lockett, G. A.; Soto‐Ramírez, N.; Zhang, H.; Venter, C.; Karmaus, W.; Holloway, J. W.; Arshad, S. H.
Abstract: Background: WHO guidelines advocate breastfeeding for 6 months, and EAACI guideline recommends exclusive breastfeeding for 4–6 months. However, evidence for breastfeeding to prevent asthma and allergic disease is conflicting. We examined whether following recommended breastfeeding guidelines alters the long‐term risks of asthma, eczema, rhinitis or atopy. Methods: The effect of nonexclusive (0, >0–6, >6 months) and exclusive breastfeeding (0, >0–4, >4 months) on repeated measures of asthma (10, 18 years), eczema, rhinitis, and atopy (1‐or‐2, 4, 10, 18 years) risks was estimated in the IoW cohort ( n = 1456) using log‐linear models with generalized estimating equations. The Food Allergy and Intolerance Research (FAIR) cohort ( n = 988), also from the IoW, was examined to replicate results. Results: Breastfeeding (any or exclusive) had no effect on asthma and allergic disease in the IoW cohort. In the FAIR cohort, any breastfeeding for >0–6 months protected against asthma at 10 years (RR = 0.50, 95% CI = 0.32–0.79, P = 0.003), but not other outcomes, whilst exclusive breastfeeding for >4 months protected against repeated rhinitis (RR = 0.36, 95% CI = 0.18–0.71, P = 0.003). Longer breastfeeding was protective against late‐onset wheeze in the IoW cohort. Conclusion: The protective effects of nonexclusive and exclusive breastfeeding against long‐term allergic outcomes were inconsistent between these colocated cohorts, agreeing with previous observations of heterogeneous effects. Although breastfeeding should be recommended for other health benefits, following breastfeeding guidelines did not appear to afford a consistent protection against long‐term asthma, eczema, rhinitis or atopy. Further research is needed into the long‐term effects of breastfeeding on allergic disease.